Incorporation of iPSCs together with TERT-immortalized keratinocytes and fibroblasts into reconstructed human gingiva enhances phenotype of gingival epithelium - Lisa-Lee Brueske; Sanne Roffel; Stephanie Beekhuis-Hoekstra; Helga E. de Vries; Susan Gibbs (PLoS ONE, 2025)
The oral mucosa plays an important role in maintaining oral and systemic health by protecting the body from harmful environmental stimuli and pathogens. Current reconstructed human gingiva models (RhG) serve as valuable testing platforms for safety and efficacy testing of dental materials, however they lack important phenotypic characteristics typical of the gingival epithelium. We aimed to determine whether incorporating induced pluripotent stem cells (iPSCs) into the hydrogel of a cell-line RhG (reconstructed epithelium on fibroblast-populated-hydrogel) would improve its phenotype. Immortalized human gingival fibroblasts were resuspended with and without iPSCs in collagen-fibrin hydrogels and gingival keratinocytes were seeded on top of the hydrogels to construct RhGs. RhGs were cultured at air-liquid interface for 1, 2, 4 and 6 weeks and extensively characterized by immunohistochemistry. In situ hybridization for X and Y chromosomes was conducted to identify female iPSCs and male fibroblasts in the RhGs. iPSC-RhGs showed increased epithelial thickening, rete ridge formation, increased cell proliferation and normalized expression of differentiation markers (keratins, involucrin, loricrin, SKALP/elafin) compared to standard RhGs, resulting in an epithelial phenotype very similar to the native gingiva. An increase in apoptotic cells was detected in iPSC-RhGs after 1 week air-exposed culture, and no iPSCs were detected in the hydrogels after 2 weeks air-exposed culture. The increase in apoptotic iPSCs after 1 week air-exposed culture correlated with an increase in keratinocyte proliferation responsible for the superior phenotype observed at 2 weeks.